2018
DOI: 10.3389/fnbeh.2018.00016
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Transcranial Direct Current Stimulation (tDCS) on Psychomotor and Visual Perception Functions Related to Driving Skills

Abstract: Objective: It could be demonstrated that anodal transcranial direct current stimulation (tDCS) of the left dorsolateral prefrontal cortex (DLPFC) enhances accuracy in working memory tasks and reaction time in healthy adults and thus may also have an influence on complex everyday tasks like driving a car. However, no studies have applied tDCS to psychomotor skills related to a standard driving test so far.Methods: 10 female and 5 male healthy adults without any medication and history of psychiatric or neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Driving is a context-dependent complex cognitive task ( 2 ) with high relevance for the daily functioning of many adults. Previous experimental studies have reported less risky driving behavior ( 3 ), improved car-following and lane-keeping ( 4 ), or no significant improvements in driving-related skills ( 5 ) after single tDCS sessions in healthy individuals. However, these results may not be generalizable to repeated tDCS sessions in patients with mental health disorders.…”
Section: Introductionmentioning
confidence: 92%
“…Driving is a context-dependent complex cognitive task ( 2 ) with high relevance for the daily functioning of many adults. Previous experimental studies have reported less risky driving behavior ( 3 ), improved car-following and lane-keeping ( 4 ), or no significant improvements in driving-related skills ( 5 ) after single tDCS sessions in healthy individuals. However, these results may not be generalizable to repeated tDCS sessions in patients with mental health disorders.…”
Section: Introductionmentioning
confidence: 92%
“…The diversity of limited-output tES used cases (for example either enhancing alertness and meditation; [ 50 52 ]) is precisely why warnings/precautions regarding use cases should be developed by each manufacturer following the risks management process described in LOTES-2017. For example, in relation to driving, tDCS has been explored to enhance driving [ 53 , 54 ], while other forms of limited output tES may be distracting (e.g., phosphenes from tACS; [ 55 , 56 ]) or specifically intended to produce drowsiness [ 17 , 57 ].…”
Section: Updates To Warnings and Precautions: General Approachmentioning
confidence: 99%
“…The diversity of limited-output tES used cases (for example either enhancing alertness and meditation; [50][51][52]) is precisely why warnings/precautions regarding use cases should be developed by each manufacturer following the risks management process described in LOTES-2017. For example, in relation to driving, tDCS has been explored to enhance driving [53,54], while other forms of limited output tES may be distracting (e.g., phosphenes from tACS; [55,56]) or specifically intended to produce drowsiness [17,57].…”
Section: Updates To Warnings and Precautions: Rationale Of Changes Fr...mentioning
confidence: 99%